2018
DOI: 10.1021/acsami.8b16434
|View full text |Cite|
|
Sign up to set email alerts
|

High Selectivities among Monovalent Cations in Dialysis through Cation-Exchange Membranes Coated with Polyelectrolyte Multilayers

Abstract: Cation-exchange membranes allow preferential passage of cations over anions, but they show minimal selectivity among cations, which limits their use in ion separations. Recent studies show that modification of cation-exchange membranes with polyelectrolyte multilayers leads to exceptional monovalent/divalent cation electrodialysis selectivities, but no studies report high selectivity among monovalent ions. This work demonstrates that adsorption of protonated poly(allylamine) (PAH)/poly(4-styrenesulfonate) (PSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…In our approach, pH is used to trigger complexation in a simple one‐step process that allows membranes with tunable pore sizes to be prepared. Poly(sodium 4‐styrenesulfonate) (PSS) and poly(allylamine hydrochloride) (PAH) are chosen as the strong and weak PEs, respectively, and because of their high charge density, they form smooth, dense, and stable complexes when mixed together . At a pH above its p K a , i.e., ≈9, PAH is uncharged and the chains exist in their collapsed coiled state .…”
Section: Introductionmentioning
confidence: 99%
“…In our approach, pH is used to trigger complexation in a simple one‐step process that allows membranes with tunable pore sizes to be prepared. Poly(sodium 4‐styrenesulfonate) (PSS) and poly(allylamine hydrochloride) (PAH) are chosen as the strong and weak PEs, respectively, and because of their high charge density, they form smooth, dense, and stable complexes when mixed together . At a pH above its p K a , i.e., ≈9, PAH is uncharged and the chains exist in their collapsed coiled state .…”
Section: Introductionmentioning
confidence: 99%
“… 188 Compared to the mono/divalent cation selectivity of bare Nafion (<2), they reported Li + /Co 2+ and K + /La 3+ selectivities exceeding 1000. Yang et al used the same approach in Donnan dialysis with (PAH/PSS) 5.5 -coated Nafion 115 membrane to differentiate within the monovalent cations and reached K + /Li + selectivity values between 8 and 60, 78 although later the authors reported lower selectivities due to variations in different batches of the Nafion membranes. 189 The selectivity was attributed to the larger hydrated radius of Li + that resulted in a lower diffusion coefficient through the dense PEM layer.…”
Section: Polyelectrolyte Multilayers On Dense Membranesmentioning
confidence: 99%
“…[15][16][17][18][19][20] The bottom-up approach of LbL assembly has been leveraged using different materials to create many active and passive functional materials, including polymer/clay anti-corrosion coatings, [21][22][23][24][25][26][27] fireretardant coatings, 28,29 nanoparticle electrocatalysts 30,31 and ion selective membranes. [32][33][34][35][36] LbL deposition of PEs offers an attractive method for modification of nanoporous membranes, which can be used to tune the ion transport properties of nanoporous membranes for various applications, ranging from water purification to energy storage and chemical separations/synthesis.…”
Section: Introductionmentioning
confidence: 99%